Analisa Perbandingan Metode Sokletasi dan Maserasi Daun Sisik Naga (Drymoglossum piloselloides (L.) C.Presl) sebagai Penyembuh Luka Sayat - Febriani, Yessi; Tambunan, Ika Julianti; Pratiwi, Nur Hanifa; Putri, Gewa Hadyaksa (Journal of Pharmaceutical and Health Research, 2025)
Dragon scale leaves (Pyrrosia piloselloides (L.) M. G. Price) have activity as antibacterial, antioxidant, antipyretic and as a febrifuge. In addition, dragon scale leaves also contain secondary metabolites such as flavonoids, polyphenols, saponins, tannins and steroids. the wound healing process includes abrasions, cuts, burns, stab wounds. The wound healing process has 3 phases, namely the inflammatory phase, proliferation phase, and maturation phase. The purpose of this study was to determine the effectiveness of total flvanoid by comparing the extraction of dragon scale leaves in healing cuts on boiler chickens (Gallus domesticus). The methods used are sokletation and maceration in the process of making thick extracts while in the research using experimental methods this research was carried out starting from the sample of dragon's scale leaves (Drymoglossum piloselloids) (L.) Presl), plant identification, making simplisia powder, making extracts, phytochemical screening, and determining total flavonoid levels using UV spectrophotometry and incision wound healing tests on broiler chickens (Gallus dzomesticus).The results of research on dragon scale leaf extracts using both maceration and sokletation methods in the process of making extractions on this plant have the same secondary metabolite content, namely flavonoids, saponins, tannins, steroids and glycosides, based on testing the total flavonoid content obtained of 3.875% in the sokletation method getting lower results compared to maceration, which is 4.235%. 235%, while in this wound test carried out by ANOVA and DUNCAN statistical methods in both methods get the same results that are significant, which means there is a significant difference between wound healing or the effect of the extract given. Dragon scale leaves with a percentage of 80% provide the best wound healing process, so it can be concluded that the two methods do not have much difference, it's just that when testing the total flavonoid content obtained the largest amount in the maceration method.